The Relationship between Family Support and Physical Activity Ability in Heart Failure Patients - Annisa Dini Aryani; Beti Kristinawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Heart failure is a condition of being unable to pump enough blood throughout the body, which can cause symptoms of fatigue and shortness of breath. These symptoms affect the physical activity of heart failure patients. Family support is one factor that can help influence the ability to engage in physical activity, especially in the daily activities of heart failure patients. This study aimed to determine the relationship between family support and physical activity in heart failure patients. This type of research uses quantitative research with a descriptive correlational design through a cross-sectional approach. It assesses family support using the PSS-Fa questionnaire and physical activity ability using the RAPA questionnaire. Sampling used a purposive sampling technique and determined the number of samples using the Slovin formula with 154 respondents. The results showed that 93 respondents (60.4%) received good family support. Optimal physical activity was 131 respondents (85.1%). The test results showed a significant p-value of 0.000 (p <0.05), which indicated a relationship between family support and physical activity ability.